Modeling and Investigation of Long-Term Performance of High-Rise Pile Cap Structures Under Scour and Corrosion - Shilei Niu; Zhongxiang Liu; Tong Guo; Anxin Guo; Sudong Xu (Journal of Marine Science and Engineering)
High-rise pile cap structures, such as sea-crossing bridges, suffer from long-term degradation due to continuous corrosion and scour, which seriously endangers structural safety. However, there is a lack of research on this topic. This study focused on the long-term performance and dynamic response of bridge pile foundations, considering scour and corrosion effects. A refined modeling method for bridge pile foundations, considering scour-induced damage and corrosion-induced degradation, was developed by adjusting nonlinear soil springs and material properties. Furthermore, hydrodynamic characteristics and long-term performance, including hydrodynamic phenomena, wave force, energy, displacement, stress, and acceleration responses, were investigated through fluid–structure coupling analysis and pile–soil interactions. The results show that the horizontal wave forces acting on the high-rise pile cap are greater than the vertical wave forces, with the most severe wave-induced damage occurring in the wave splash zone. Steel and concrete degradation in the wave splash zone typically occurs sooner than in the atmospheric zone. The total energy of the structure at each moment under load is equal to the sum of internal energy and kinetic energy. Increased corrosion time and scour depth result in increased displacement and stress at the pile cap connection. The long-term dynamic response is mainly influenced by the second-order frequency (62 Hz).